1990
DOI: 10.2105/ajph.80.1.61
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of the initiation of psychotherapeutic medicine use.

Abstract: This study examined the hypothesized predictive association between illicit drug use and the onset of prescribed psychotherapeutic medicine use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Consistent with hypothesis 1 and a small body of prior evidence (24,25,40), the analyses for this study identified illicit drug use as a risk factor for initiation of psychotherapeutic medicine use among both genders. The estimated relative risk was larger among men (RR = 4.01) than women (RR = 2.21).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Consistent with hypothesis 1 and a small body of prior evidence (24,25,40), the analyses for this study identified illicit drug use as a risk factor for initiation of psychotherapeutic medicine use among both genders. The estimated relative risk was larger among men (RR = 4.01) than women (RR = 2.21).…”
Section: Discussionsupporting
confidence: 81%
“…Along these lines, Yamaguchi & Kandel (24) showed an association between illicit drug use and increased risk of psychotherapeutic medicine use among males, which was also present, but to a lesser extent, among females. Trinkoff et al (25) also found that illicit drug use predicted psychotherapeutic medicine use in a household sample of 18-to 44-year-olds. This relationship was not mediated by the occurrence of psychiatric symptoms.…”
mentioning
confidence: 93%
“…In summary, current alcohol, tobacco, and cannabis use is associated with psychotherapeutic nonmedical use of drugs by older Americans adults. This pattern of drug use is similar to that found in youth and young adults, where cannabis users have been found to be more likely to use other drugs 6 and users of illicit drugs have been found to be two and a half times more likely to receive a prescription for psychotherapeutic medicine use 7 . These findings emphasize the need for continued efforts to understand correlates and risk factors for drug use in older adults.…”
Section: Drug Involvement In the Previous Year Of Americans Aged 50supporting
confidence: 79%
“…There is little or no evidence that women seek drugs more assertively than do men (Russo, 1990;Trinkoff;Anthony, & Munoz, 1990), although their more favorable attitudes toward mental health treatment might plausibly lead to greater compliance with drug recommendations.…”
Section: Drug Prescription Practicesmentioning
confidence: 99%